PERENCANAAN INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) INDUSTRI TAHU DI KECAMATAN DENDANG KABUPATEN TANJUNG JABUNG TIMUR - Marhadi Marhadi (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
Tofu factory in the district Dendang factory on an industrial scale is generally managed the household. In one day this factory uses raw materials such as soybeans (Grylin Spp) of 50 kg and the results obtained only marketed around the District Dendang. The volume of waste generated over 2.25 to 5 m³ / day. Mr. Ahmad Yamin’s tofu factory is one of the largest factories in the district Dendang, Tanjung Jabung Timur has characteristics of pH wastewater, TSS, NH3-N, BOD, COD, NO3, NO2, sequence 5, 34, 329 mg / l, 03:49 mg / l, 581 mg / l, 1228 mg / l, 1.3629 mg / l, 1.3771 mg / l. Some wastewater parameters have been tested exceed the quality standards appropriate to KEPMENLH NO 51, 1995. Generally, the wastewater can pollute the environment out either physically, chemically and biologically. It is necessary to develop wastewater treatment technologies that are simple, low cost, easy operation and has a high processing efficiency of pollutants. One alternative biofilter wastewater using anaerobic aerobic reactor is developed with the principles of microbial growth and attached to the filter media and form a layer biofilm. Data collection methods used are field surveys, documentation, literature review and alaisis laboratory to determine the characteristics of water limbah.Hasil waste discharge planning calculation for 25 (twenty five) years is 38.18 m3 / dayKey word : Liquid Waste Know, anaerobic-aerobic biofilter.